2013
DOI: 10.1021/ic400878k
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Complexes of Nucleoside-5′-Phosphorothioate Analogues with Zinc Ions

Abstract: On the basis of the high affinity of Zn(2+) to sulfur and imidazole, we targeted nucleotides such as GDP-β-S, ADP-β-S, and AP3(β-S)A, as potential biocompatible Zn(2+)-chelators. The thiophosphate moiety enhanced the stability of the Zn(2+)-nucleotide complex by about 0.7 log units. ATP-α,β-CH2-γ-S formed the most stable Zn(2+)-complex studied here, log K 6.50, being ~0.8 and ~1.1 log units more stable than ATP-γ-S-Zn(2+) and ATP-Zn(2+) complexes, and was the major species, 84%, under physiological pH. Guanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Ap 3 (β-S)A, 7-Zn 2+ (log K = 5.74/6.5 vs. 3.8, respectively). 15 Subsequently, we reported that an additional terminal phosphate group on the AMP/GMP scaffold, as in 2′-deoxy-adenosine/guanosine-3′,5′-bisphosphate, resulted in a 1.8-and 2.8-fold increased Fe 2+ chelation as compared to adenosine/guanosine-5′-monophosphate, respectively. 16 Hence, we hypothesized that enhanced Fe 2+ or Zn 2+ chelation is due to the presence of two terminal phosphate groups in d(pNp) vs. one terminal phosphate group in NMP analogues, 16 or one terminal phosphate in ATP vs. no terminal phosphate in Ap 3 A.…”
Section: Introductionmentioning
confidence: 99%
“…Ap 3 (β-S)A, 7-Zn 2+ (log K = 5.74/6.5 vs. 3.8, respectively). 15 Subsequently, we reported that an additional terminal phosphate group on the AMP/GMP scaffold, as in 2′-deoxy-adenosine/guanosine-3′,5′-bisphosphate, resulted in a 1.8-and 2.8-fold increased Fe 2+ chelation as compared to adenosine/guanosine-5′-monophosphate, respectively. 16 Hence, we hypothesized that enhanced Fe 2+ or Zn 2+ chelation is due to the presence of two terminal phosphate groups in d(pNp) vs. one terminal phosphate group in NMP analogues, 16 or one terminal phosphate in ATP vs. no terminal phosphate in Ap 3 A.…”
Section: Introductionmentioning
confidence: 99%
“…Analog 7, although more potent than 6, showed less selectivity for NPP1. Analog 6 (at 100 μM) only slightly inhibited NPP3, NTPDase1, and NTPDase3 (38, 0, 22%) [13,44].…”
Section: Introductionmentioning
confidence: 95%
“…Recently, we have reported the ability of ATP-g-S-(a,b-CH 2 ) to dissolve Ab 40 -Cu(I) and Ab 42 -Cu(II)/Zn(II) aggregates, much more effectively than ATP-g-S, ATP, or EDTA [10]. We have also determined its high affinity to Zn(II)-ions [16]. Hence, we assume that the ability of ATP-g-S-(a,b-CH 2 ) to dissolve Ab-M(II) aggregates, and consequently rescue neurons from Ab toxicity, results from metal-ions chelation.…”
Section: Discussionmentioning
confidence: 94%
“…The highly promising properties of ATP-g-S-(a,b-CH 2 ) as a Fenton reaction inhibitor [10], an effective ion chelator [16], a powerful agent for in-vitro dissolution of Ab 40/42 -M(II) oligomers and aggregates [10], together with its enzymatic stability, and its high activity at P2Y11-R [12], encouraged us to explore the potential of ATP-g-S-(a,b-CH 2 ) for the rescue of primary neurons subjected to insults typical of Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%